Technology Acceptance Model (TAM): A Bibliometric Analysis from Inception - Gupta, Swati; Abbas, Alhamzah Fadhil; Srivastava, Rajeev (Journal of Telecommunications and the Digital Economy, 2022)
The technology acceptance model (TAM) has long-term implications for management studies. However, the evolution of the literature on technology acceptance ideas received very little attention in the bibliographic review. Few research reviews provided a systematic overview of the development and progress of the TAM literature based on the entire citation network, while many research reviews focused on re-examining the links between TAM components through meta-analysis. This study investigates: a) how TAM research has evolved and expanded over the last 30 years; b) the main areas in which the TAM model has been used; and c) key contributors to TAM research and their collaborations. This bibliometric analysis was carried out based on 8207 papers published in the Scopus database between 1990 and 2020 to assess the feasibility of the model and its applicability. The findings revealed that early TAM research was conducted both by Eastern and Western scholars and that it has since continued to evolve and be shared widely. Nonetheless, most TAM publications have focused on the same narrow domains of computer science, social science, business, management, and accounting and the trendiest topics were usefulness, trust, ease of use, e-learning, adoption, e-commerce, and social media.